Meaning of life and death during COVID-19 pandemic: A cultural and religious narratives - Wonke Buqa (HTS Teologiese Studies/Theological Studies, 2024)
The sudden arrival of the coronavirus disease 2019 (COVID-19) pandemic in South Africa drastically changed the normal way of life in all sectors. It compelled everyone to look at the meaning of life and death differently and more painfully than before. This article investigates the cultural theories and religious narratives on the meaning of life and death, associated with the pervasiveness of the COVID-19 pandemic. The coronavirus affected individuals, families and communities, some directly or indirectly, no one is or was immune to the virus. The article argues that due to COVID-19 restrictions and lockdowns, culture, religious practices and protocols have been upended. The COVID-19 pandemic challenged inkcubeko nenkolo yabantu [culture, people’s religious belief systems and practices]. This article consists of in-depth qualitative interviews with four religious leaders from the Christian and Muslim faiths. Because of the interviews with persons, oral historians conduct open-ended interviews, as a form of social inquiry. Oral history narratives thus connect the individual and the social, drawing on cultural and religious expressions to tell one’s story.